Karakteristik Briket Fly Ash Batubara Berdasarkan Campuran Biomassa Arang Tempurung Kelapa Dan Serbuk Jati Belanda - Muhamad, Zein; Pratowo, Bambang; Nawawi, Abdul Rohim (Riviera Publishing, 2025)
The increasing energy demand and the high amount of coal waste in the form of fly ash encourage the development of environmentally friendly alternative fuels. This study aims to determine the process of making fly ash-based briquettes, assess the water content, ash content, burning time, and compare the characteristics of hardness and calorific value of briquettes mixed with coconut shell charcoal and Dutch teak wood powder. In this study, briquettes were made by mixing fly ash and coconut shell charcoal and fly ash and Dutch teak wood powder with compositions of 20:70, 40:50, 45:45, and 30:60 with a 10% adhesive concentration. The research process was carried out by manually mixing the materials until homogeneous, molding using a block-shaped metal mold, then drying in an oven at a temperature of 100–105°C for 3 hours. Testing methods include testing water content, ash content, calorific value, compressive strength, and burning time. The experimental data are explained comparatively to the composition variations. The results showed that briquettes with a composition of 40% fly ash, 50% coconut shell charcoal, and 10% adhesive produced the highest calorific value of 6,215 kcal/kg and a compressive strength of 2,048 kg/cm², superior to the mixture of teak wood powder.